The Influence of the Convention on the Rights of Persons with Disabilities on Canadian Jurisprudence in the First Decade Since its Ratification - De Marinis, Jessica; Joffe, Kerri; Weiner, Rachel (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2022)
Canada’s ratification of the United Nations Convention on the Rights of Persons with Disabilities [CRPD]in 2010 was met with hope and excitement that it would lead to much-needed improvements in equality, inclusion and accessibility for persons with disabilities in Canada. This paper explores the impact the CRPD has had on Canadian jurisprudence in the decade since Canada ratified the treaty. Our analysis of the jurisprudence indicates that Canadian courts and tribunals have employed a variety of approaches to the CRPD, for which we provide illustrative examples. Overall, the CRPD has impacted the reasoning or outcome in a small number of cases, but has not exerted great influence in Canadian jurisprudence to date. Despite this limited impact, a number of emerging factors suggest that the CRPD may well become more influential in Canadian jurisprudence in the future.